The Escalation of Commitment To a Course of Action - Staw, Barry M. (Academy of Management Review, 1981)
There are many instances in which individuals can become locked into a costly course of action. Because it is often possible for persons who have suffered a setback to recoup their losses through an even greater commitment of resources to the same course of action, a cycle of escalating commitment can be produced. In this paper, I review recent research on the escalation of commitment and try to integrate its complex and often conflicting determinants.